Technology Entrepreneurship Project (ENT 600) : Biochar / Nur Syamimi Mohamad Abdul Adzis - Mohamad Abdul Adzis, Nur Syamimi; Mat Razaman, Najiha; Abdul Aziz, Ami Azida; Azhar, Rahil; Mohd Razip, Dhurra Izzah; Ibrahim, Nur Rahimah (2022)
Agro Living Sdn Bhd is a Malaysian multinational company that engaged in the plantation and cultivation development, fertilizer, pots and seedlings. One of the highest requested product is fertilizer. Fertilizer is known as a substance or material that is applied to soil or to plant tissue to supply plant nutrients. However, chemical fertilizer cannot bring satisfaction to consumers especially farmers as the water way may be contaminated with chemicals. Our company has come out with a possible product to improve the fertilizer. Agro Living has provides a solution to the demand of superior fertilization with its unique biochar product, which named as Biochar fertilizer. This biochar is made from the biomass which contains a lot of natural nutrients. This product results in greater soil nutrient, regeneration and crop yields. Besides, our company also use plastic waste also to produce the biochar together with the biomass. Besides innovating and improving a fertilizer, we also want to promote to build a green product where we reuse the plastic waste instead of leave dumped everywhere. This may allowing Agro Living Sdn Bhd to be uniquely positioned to build thousands dollar company and get a lots of attention from people within months of opening its door. By doing this new product development, it will help us to improve more on our new product which is Biochar fertilizer. New product development refers to the initial steps in the development of a new product or service. This is essential to any business that must keep up with market trends and changes. Furthermore, the process of developing a new product can be divided into five stages: research and development, product design/features, idea testing, prototype development, and test marketing. To develop the product and satisfy consumer needs and wants, idea screening, idea generating, SWOT analysis, and concept testing were carried out. Finally, market testing was performed in test marketing to ensure that this product was approved by the community. Market testing was carried out to determine whether a product can be accepted by users and earn a profit in today's market.